MnSOD protects against COX1-mediated endothelial dysfunction in chronic heart failure - Miller, Jordan D. (American Physiological Society, 2010)
Endothelial function is impaired by oxidative stress in chronic heart failure (HF). Mechanisms that protect against increases in oxidative stress in HF are not clear. The goal of this study was to determine whether manganese superoxide dismutase (MnSOD) plays a key role in protecting against endothelial dysfunction in HF. Endothelial function and gene expression were examined in aorta from wild-type mice (MnSOD(+/+)) and mice deficient in MnSOD (MnSOD(+/−)) 12 wk after ligation of the left coronary artery (LCA). LCA ligation produced similar size myocardial infarctions in MnSOD(+/+) and MnSOD(+/−) mice and reduced ejection fraction to ∼20% in both groups. Maximal relaxation in response to acetylcholine was 78 ± 3% (mean ± SE) and 66 ± 8% in sham-operated MnSOD(+/+) and MnSOD(+/−) mice, respectively. Expression of antioxidant enzymes increased in MnSOD(+/+) mice with HF, and maximal relaxation to acetylcholine was slightly impaired (68 ± 4%). Greater endothelial dysfunction was observed in MnSOD(+/−) mice with HF (46 ± 5%, P < 0.05), which was significantly improved by polyethylene glycol-catalase but not Tempol. Incubation with the nonspecific cyclooxygenase (COX) inhibitor indomethacin or the COX1 inhibitor valeryl salicylate, but not the COX-2 inhibitor NS-398, significantly improved relaxation to acetylcholine in HF mice (maximum relaxation = 74 ± 5, 91 ± 1, and 58 ± 5%). These data suggest that MnSOD plays a key role in protecting against endothelial dysfunction in HF. A novel mechanism was identified whereby chronic increases in oxidative stress, produced by mitochondrial SOD deficiency, impair vascular function via a hydrogen peroxide-dependent, COX1-dependent, endothelium-derived contracting factor.